Non Communicable Diseases - Abstracts of Poster Presentations (Nepal Journal of Epidemiology, 2014)
Abstracts of the Poster Presentations at the session on Non Communicable Diseases at the International Conference on Research Methodology and Research Writing (ICRMSW) 2013. DOI: http://dx.doi.org/10.3126/nje.v4i2.10165